SWEARWORDS, FEELINGS AND EMOTIONS - Mulatsih, Devi (Perspective Jurnal Pendidikan Bahasa Inggris, 2013)
This article analyzes the use of swearwords with reference to Sociolinguistic, and Psychological conceptual frameworks. It starts with an emotions and feelings when one is expected to be careful in selecting the words to express his/her thoughts. In the guise of tackling the problem, Sociolinguistic and Psychological explanation is pursued, which in the end, shows that Sociolinguistic explanation is not really adequate to handle the issue. This relates to the possible notion that swearwords might be enacted as a (very) personal expression, devoid of any physical addressees. Key words: swearwords, Sociolinguistic.